Comparing the financial reporting quality of Chinese and US public firms. Issue 4 (11th April 2018) - Brown, Kareen; Elayan, Fayez A.; Li, Jingyu; Liu, Zhefeng
Abstract : Purpose: The purpose of this paper is to investigate whether US regulatory actions around reverse mergers (RM) have exerted any spillover effects on the Chinese firms listed in China and whether Chinese firms have exhibited lower financial reporting quality than their US counterparts. Design/methodology/approach: To test the possible spillover effect, this paper calculates three-day cumulative average abnormal returns (CAAR) and the aggregate CAAR for a series of US regulatory actions in 2010 and 2011. The study then compares the accrual quality, conditional conservatism, and information content of accruals of Chinese firms and US firms. Findings: The paper documents a spillover effect of US actions around RM on Chinese stocks listed in China. Overall results do not support the perception that Chinese firms have lower financial reporting quality than their US counterparts. Research limitations/implications: While this study provides evidence consistent with investors perceiving poor financial reporting quality among Chinese firms, that perception is not justified by empirical evidence. Practical implications: Investors need not be overly concerned about the financial reporting quality among the Chinese firms when they make asset allocation decisions. Social implications: A reality check is important given that perceptions may be outdated, biased, misleading, and costly. Originality/value: This study puts the financial reporting quality of Chinese firms into perspective helping global investors assess information risk for optimal resource allocation.